You've got mail! - written communication and feedback in mathematics - Barbosa, Ana (2021)
This paper describes a study that aims to understand and characterize the written communication of future teachers through a pen pal experience with elementary education students, in particular the nature of their feedback. To carry out this investigation we followed a qualitative methodology and collected data through observation, interviews and written productions. The participants were seven pre-service teachers that attended a Master’s Degree Course in Primary Education (6-12 years old) who interacted through letter correspondence with 3rd grade students. Results show that the pre-service teachers valued this experience, considering it useful and effective in the development of written communication. They also had the opportunity to identify the importance of more general aspects, such as the adequacy of the discourse, the need to acknowledge the curricular guidelines and the features of the educational context. The type of feedback given in the written commentaries was diversified, trying to meet the main characteristics of evaluative writing, being intentional, personalized and identifying aspects to improve through self-regulation.